Investigation of METTL3 as an inhibitor of kanamycin-induced ototoxicity via stress granule formation - Wu, Yan; Huang, Yu-Yu; Wang, Lu-Yao; Yang, Yan; Cui, Fei-Lun; Li, Shu-Na (Frontiers in Pharmacology, 2024)
Background: Methyltransferase-like 3 (METTL3), a component of the N6-methyladenosine (m6A) methyltransferase family, exhibits significant expression in HEI-OC1 cells and cochlear explants. Aminoglycoside antibiotics, known for their ototoxic potential, frequently induce irreversible auditory damage in hair cells, predominantly through oxidative stress mechanisms. However, the specific role of METTL3 in kanamycin-induced hair cell loss remains unclear. Objective: This study aims to elucidate the mechanisms by which METTL3 contributes to kanamycin-induced ototoxicity. Methods and Results: In vivo experiments demonstrated a notable reduction in METTL3 expression within cochlear explants following kanamycin administration, concomitant with the formation of stress granules (SGs). Similarly, a 24-hour kanamycin treatment led to decreased METTL3 expression and induced SG formation both in HEI-OC1 cells and neonatal cochlear explants, corroborating the in vivo observations. Lentivirus-mediated transfection was employed to overexpress and knockdown METTL3 in HEI-OC1 cells. Knockdown of METTL3 resulted in increased reactive oxygen species (ROS) levels and apoptosis induced by kanamycin, while concurrently reducing SG formation. Conversely, overexpression of METTL3 attenuated ROS generation, decreased apoptosis rates, and promoted SG formation induced by kanamycin. Therefore, METTL3-mediated SG formation presents a promising target for mitigating kanamycin-induced ROS generation and the rate of apoptosis. Conclusion: This finding indicates that METTL3-mediated SG formation holds potential in mitigating kanamycin-induced impairments in cochlear hair cells by reducing ROS formation and apoptosis rates.